Tren Penelitian Pendidikan Matematika di Jurnal Mosharafa: Jurnal Pendidikan Matematika Tahun 2021-2022 - Ice Dwi Novelza; Nia Monika Sari; Aan Putra (Program Studi S1 Matematika UNESA, 2023)
The publication of the results of mathematics education research has increased and developed from time to time, especially in accredited national journals. This study aims to provide an overview of research trends in mathematics education published in Mosharafa : Jurnal Pendidikan Matematika which accredited on grade Sinta 2 and to identify opportunities for future mathematics education research. This research is a scoping literature review using the five-stage framework of Arksey & O'Malley. A review was conducted of 90 articles in the field of mathematics education published in Mosharafa : Jurnal Pendidikan Matematika in 2021-2022 period. Based on the results and discussion, it shows that the trend of mathematics education journals (2021-2022) in Mosharafa : Jurnal Pendidikan Matematika is the dominant research topic used, namely regarding the ability to think mathematically, while research topics that are minimally used include book analysis. The dominant research subjects used were junior high school students, while the minimum was the general public. The dominant research methods used are qualitative research and quantitative research. While the recommendations that the dominant researcher suggests are regarding further researchers being able to apply, develop and examine more deeply the research that has been carried out and the next researcher should apply new and interesting variations to the research that will be carried out.